Fetal and neonatal cardiac rhabdomyomas: clinical presentation, outcome and association with tuberous sclerosis complex - Atalay, Semra; Aypar, Ebru; Uçar, Tayfun; Altuğ, Nahide; Deda, Gülhis; Teber, Serap; Tutar, Ercan (The Turkish Journal of Pediatrics, 2010)
Rhabdomyoma is the most common pediatric heart tumor. Cardiac rhabdomyomas (CRs) have a natural history of spontaneous regression and are closely associated with tuberous sclerosis complex (TSC). We aimed to evaluate the clinical presentation and outcome of CRs and their association with TSC. Patients with CRs diagnosed in last six years were retrospectively analyzed. A total of 25 tumors were identified in seven patients by echocardiography. Three patients were diagnosed prenatally by fetal echocardiography, three patients in the neonatal period and one patient in early infancy. The median followup period was two years (range: 5 months-6 years). Five patients (71%) had multiple tumors. Three patients had arrhythmias and two patients required surgery. Only 36% (9/25) of the tumors regressed. TSC was diagnosed in four patients during the follow-up. CRs may have different presentations and clinical course. Surgery is only necessary when hemodynamically significant obstruction is present. As CRs are associated with long-term development of TSC and other diagnostic features are not yet typically apparent in the prenatal and neonatal periods, careful evaluation and follow-up are essential to exclude TSC.